Clinical preventive-based best practices to reduce the risk of peristomal skin complications – an international consensus report - Gillian Down, & Kimberly Bain, & Birgitte Dissing Andersen, & Lina Martins, & Tonny Karlsmark, & Gregor Jemec, & Mark Bain, & Lene Feldskov Nielsen, & Cecilie Jaeger Leidesdorff Bechshoeft and & Anne Steen Hansen (WCET Journal - French Edition, 2023)
Evidence indicates that peristomal skin complications (PSC) are a common problem for people with an ostomy and have serious implications on their overall health and quality of life. While there is evidence and documentation on the cause and effect of PSC, there is little written on the risk factors or on how to maintain peristomal skin integrity and prevent PSC. To address this gap, a panel of ostomy experts was convened to conduct a process to reach an international consensus on PSC risk factors. A large-scale modified Delphi consensus-building process was conducted between September 2019 and October 2020. A total of 4,285 online survey responses were received from 36 countries across six continents. The result was a consensus focused on the prevention of PSC and on the individual patient risk factors healthcare providers should consider when determining the best pouching system and care plan for ostomy patients. The consensus supported the development of a PSC risk factor model. The model was subsequently ratified in October 2020. The purpose of the model is to help guide healthcare providers in assessing the risk factors for developing a PSC for each patient and ultimately guide healthcare providers to prevent skin damage, maintain healthy peristomal skin, and support the overall health, wellbeing and quality of life of ostomy patients.